Community resilience and wellbeing in Northwest Russian forestry settlements - Södor, Uuve (2011)
Based on the rich, descriptive data of existing ethnographic accounts this study observes the transformation of the Russian forestry sector, and explores the aspects of community resilience in three different forestry settlements in Northwest Russia. According to the retrospective analyses employed, the earlier success of those communities was formed since the time of early industrialisation by a symbiotic coexistence with a local harvesting enterprise. The period of turbulent transformations in the 1990s, however, significantly changed the livelihood patterns of the studied forestry settlements. This research focuses on the social changes that the technological and economic transformation of forestry sector has brought about. It also notes the new trends related to local employment, the changing roles of forestry enterprises and forestry villages on the basis of extensive empirical research. The study thus evaluates several topical issues of today's forestry complex and provides insights into the current developmental pathways of today's Russian forest industry from the perspective of forestry settlements and local development. Finally, the study assesses the perspectives for local sustainability by mapping out community resilience.